Legal Force of Transfer of Home Ownership Loans (KPR) from Debtors to Third Parties without Approval from The Bank - Susilowardani, Susilowardani (Ann Publisher, 2023)
Ownership of a house is now a benchmark as a form of primary needs of an individual and is used as land to invest because it has a relatively high economic value. It will be tough for low-income people to own a house by buying it in cash. For some people, building a house must incur relatively high costs. Therefore, banks provide financing funds so that people can own houses. One form of financing from banks is Home Ownership Credit or KPR. However, implementing homeownership loans (KPR) has various problems, including transferring rights to the object of home ownership loans (KPR) or mortgage loan offers. So the problem arises: How is the legal force of transferring home ownership loans (KPR) from debtors to third parties without approval from the bank? This research uses research methods in the form of descriptive analysis. The act of credit oper underhand, whether it is a sale, transfer, or anything carried out by the debtor without permission or the knowledge of the creditor or bank, is included in the type of violation, and the agreement is also not binding on third parties or new debtors. If the debtor makes the transfer before repayment at the bank, then the agreement made by the debtor to a third party is null and void.